1998
DOI: 10.1046/j.1523-1747.1998.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

A Variable Monilethrix Phenotype Associated With a Novel Mutation, Glu402Lys, in the Helix Termination Motif of the Type II Hair Keratin hHb1

Abstract: Monilethrix is a rare human hair disorder with autosomal dominant transmission that can be caused by mutations in hair keratins. Up until now, pathogenic mutations in the type II hair cortex keratins hHb6 and hHb1 were restricted to a highly conserved glutamic acid residue Glu413 (Glu117 of the 2B subdomains) in the EIATYRRLLEGEE helix termination motif of the two keratins. The critical glutamic acid residue was substituted either by a lysine or, less frequently, by an aspartic acid residue. Here we report a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 20 publications
5
31
0
2
Order By: Relevance
“…8b). In this respect, it is highly astonishing that the impact of a disruptive mutation in a cortex keratin, hHb1 or hHb6, is obviously not attenuated by the high number of paralleling unaffected keratin pairings but entails such dramatic alterations as the beaded-hair phenotype in Monilethrix patients (33,34).…”
Section: Resultsmentioning
confidence: 99%
“…8b). In this respect, it is highly astonishing that the impact of a disruptive mutation in a cortex keratin, hHb1 or hHb6, is obviously not attenuated by the high number of paralleling unaffected keratin pairings but entails such dramatic alterations as the beaded-hair phenotype in Monilethrix patients (33,34).…”
Section: Resultsmentioning
confidence: 99%
“…11 A form of alopecia, monilethrix (MIM 158000), was localized to chromosome 12q13 and is due to mutations in the hair cortex keratin gene HB1 or HB6. 12 The severity of alopecia is variable from patient to patient and is also variable over time in the same individual. Perifollicular hyperkeratosis is a consistent feature of monilethrix.…”
Section: Introductionmentioning
confidence: 99%
“…Both can be divided into type I (acidic) and type II (basic-neutral) proteins that form the 10-nm intermediate filament network of epithelial cells by obligatory association of equimolar amounts of type I and type II keratins (1,2). Disturbances of intermediate filament formation through deleterious mutations in keratins can lead to a weakening of the structural integrity of the respective epithelial cells, resulting in hereditary disorders of skin, mucosa, nail, or hair (3)(4)(5)(6)(7). Although initial studies of hair keratin proteins of several species indicated the existence of eight major type hair keratins, four type I members, termed Ha1-Ha4, and four type II members, termed Hb1-Hb4, as well as of one minor hair keratin pair, Hax/Hbx (8 -11), it has recently been shown that the hair keratin family is distinctly more complex.…”
mentioning
confidence: 99%